2019
DOI: 10.12784/nzcomjnl55.2019.5.35-43
|View full text |Cite
|
Sign up to set email alerts
|

Using critical discourse analysis and the concept of food security to understand pregnant women’s nutrition in Aotearoa/New Zealand

Abstract: Background: Increasingly, pregnant women in Aotearoa/New Zealand (Aotearoa) are unable to achieve the dietary intakes recommended by the Ministry of Health (MOH). While health professionals express frustration at "being the ambulance at the bottom of the cliff", the continued government response to this public health concern is to "educate women", as per the current mantra of personal responsibility and choice-based rhetoric. Aim: Using critical discourse analysis (CDA), this study examined the discourses rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Poor nutrition, obesity and food insecurity become particularly significant during pregnancy. In South Auckland, the high number of morbidly obese pregnant women has become the new normal (Counties Manukau District Health Board [CMDHB], 2013[CMDHB], , 2019Raven & Stewart-Withers, 2019).…”
Section: Literature Review Nutrition Food Insecurity and Obesity Ovementioning
confidence: 99%
See 2 more Smart Citations
“…Poor nutrition, obesity and food insecurity become particularly significant during pregnancy. In South Auckland, the high number of morbidly obese pregnant women has become the new normal (Counties Manukau District Health Board [CMDHB], 2013[CMDHB], , 2019Raven & Stewart-Withers, 2019).…”
Section: Literature Review Nutrition Food Insecurity and Obesity Ovementioning
confidence: 99%
“…Based on their critical discourse analysis of 30 government, media and academic documents, Raven and Stewart-Withers (2019) argue that society regards pregnant women as being solely responsible for their own nutrition. They argue that, in fact, for some women malnutrition is more the result of food insecurity and disempowerment.…”
Section: Literature Review Nutrition Food Insecurity and Obesity Ovementioning
confidence: 99%
See 1 more Smart Citation
“…In Aotearoa New Zealand, found that most pregnant women do not follow the current nutritional guidelines for pregnancy, with only 3% meeting the recommendations for the four identified food groups. Food insecurity is a major barrier to a healthy pregnancy, with food purchase often less a priority than rent and/or heating (Abrahams, Lund, Field, & Honikman, 2018;Raven & Stewart-Withers, 2019;van den Heuvel & Birken, 2018).…”
Section: Health and Lifestylementioning
confidence: 99%
“…Blaming pregnant women for their obesity is termed maternal responsibilization by Parker (2014). It has been argued that this blaming has halted progress around obesity and instead resulted in individualised stigmatisation, siloed approaches to care, political inaction, and an absence of coherent strategies within food and health systems (Ralston et al, 2018;Raven & Stewart-Withers, 2019). Seeing obesity as a self-deficient behaviour, pressures women to engage and conform to medicalised approaches (Knight-Agarwal et al, 2014;Raven & Stewart-Withers, 2019).…”
Section: Individual Vs Collective Responsibility For Obesity Dichotomymentioning
confidence: 99%